Salmonella associated with agricultural animals exhibit diverse evolutionary rates and show evidence of recent clonal expansion - Ruixi Chen; Linghuan Yang; Magdalena S. Pajor; Martin Wiedmann; Renato H. Orsi (mBio)
ABSTRACT Most foodborne salmonellosis outbreaks are linked to agricultural animal products with a few serovars accounting for most Salmonella isolated from specific animal products, suggesting an adaptation to the corresponding animal hosts and their respective environments. Here, we utilized whole-genome sequence (WGS) data to analyze the evolution and population genetics of seven serovars frequently isolated from ground beef (Montevideo, Cerro, and Dublin), chicken (Kentucky, Infantis, and Enteritidis), and turkey (Reading) in the United States. In addition, publicly available metadata were used to characterize major clades within each serovar with regard to public health significance. Except for Dublin, all serovars were polyphyletic, comprising 2–6 phylogenetic groups. Further partitioning of the phylogenies identified 25 major clades, including 12 associated with animal or environmental niches. These 12 clades differed in evolutionary parameters (e.g., substitution rates) as well as public health relevant characteristics (e.g., association with human illness, antimicrobial resistance). Overall, our results highlight several critical trends: (i) the Salmonella generation time appears to be more dependent on source than serovar and (ii) all serovars contain clades and sub-clades that are estimated to have emerged after the year 1940 and that are enriched for isolates associated with humans, agricultural animals, antimicrobial resistance (AMR), and/or specific geographical regions. These findings suggest that serotyping alone does not provide enough resolution to differentiate isolates that may have evolved independently, present distinct geographic distribution and host association, and possibly have distinct public health significance.IMPORTANCENon-typhoidal Salmonella are major foodborne bacterial pathogens estimated to cause more than one million illnesses, thousands of hospitalizations, and hundreds of deaths annually in the United States. More than 70% of Salmonella outbreaks in the United States have been associated with agricultural animals. Certain serovars include persistent strains that have repeatedly contaminated beef, chicken, and turkey, causing outbreaks and sporadic cases over many years. These persistent strains represent a particular challenge to public health, as they are genetically clonal and widespread, making it difficult to differentiate distinct outbreak and contamination events using whole-genome sequence (WGS)-based subtyping methods (e.g., core genome allelic typing). Our results indicate that a phylogenetic approach is needed to investigate persistent strains and suggest that the association between a Salmonella serovar and an agricultural animal is driven by the expansion of clonal subtypes that likely became adapted to specific animals and associated environments.